Factors Affecting Hanoi Students ' Decisions to Choose University to Study Information Technology Major - Trinh, Van Huy; Le, Thi Mai; Hoang, Hanh Nguyen; Vu, Van Hieu (Formosa Journal of Computer and Information Science, 2024)
This study explores the factors influencing Hanoi high school students' decisions to choose a university for studying Information Technology (IT) amidst the rapidly growing IT industry, especially following the 4.0 industrial revolution. The study employs quantitative methods, analyzing a sample of 241 students currently enrolled in IT programs across Hanoi. Key findings reveal that factors such as tuition fees, family recommendations, alumni influence, and university reputation significantly impact students' intentions and decisions. Interestingly, while university reputation positively influences students' intentions, it does not necessarily lead to their final decision to enroll. In contrast, financial considerations and advice from trusted sources play a more pivotal role. Additionally, the study finds that gender and admission scores do not significantly affect the decisionmaking process for these students. The results offer practical insights for universities to refine their recruitment and marketing strategies, ensuring they align with the real-world factors that influence student choice. By understanding these dynamics, universities can better attract and retain students in IT programs, thereby meeting the growing demands of the IT sector